Neutrophil-to-Lymphocyte Ratio as an Inflammatory Marker in Familial Mediterranean Fever: A Systematic Review and Meta-analysis - Omranzadeh, Alireza; Baradaran, Ashkan; Ghodsi, Alireza; Arekhi, Soheil; Dadgarmoghaddam, Malihe; Mirshekaran, Amin; Tarazjani, Amirreza Dehghan; Fazeli, Bahare (Journal of Child Science, 2021)
Familial Mediterranean fever (FMF) is a genetic disease with inflammatory basis. Several studies have assessed the role of neutrophil-to-lymphocyte ratio (NLR) in detecting this inflammation; however, no systematic review or meta-analysis has assessed these studies together. The aim of this study is to systematically review and meta-analyze the NLR value between FMF patients and normal controls. Scopus, PubMed, Embase, and ISI Web of Science were searched using predesigned search strategy to find the studies that assessed NLR in FMF patients and compared the value with normal controls. There was no time limitation. Finally, two researchers extracted data including first author name, publication year, the country, study design, number of patients and controls, time of disease diagnosis, FMF diagnostic criteria, mean age of the patients, and the NLR value. The data were systematically reviewed and meta-analyzed. In total, 464 articles were found on search; however, only 12 studies qualified for enrollment in the systematic review and 10 studies, with appropriate effect size, in the meta-analysis. These studies were conducted between 2013 and 2019. Eleven studies were conducted in Turkey and one in Egypt. Out of 12 studies, 9 had enrollment criteria for FMF patients: 8 studies used Tel Hashomer criteria and 1 study used Yalçinkaya–Özen criteria. All studies, except for two, had genetic confirmation for FMF. The mean NLR values in attack-free (standard difference in means = 0.482; p < 0.0001) and attack groups (standard difference in means = 0.853; p = 0.001) were significantly higher than control group. The mean NLR value may be related to the underlying inflammation in FMF.
Keywords: familial Mediterranean fever; neutrophil-to-lymphocyte ratio; inflammation